A SEM-based research on influencing factors of team situation awareness in nuclear power plants - Wang, Ru; Wen, Jing; Li, Pengcheng (Frontiers in Energy Research, 2022)
Team situation awareness (TSA) is one of the key factors that affect team decision-making and implementation. TSA is influenced by performance shaping factors (PSFs) in digital nuclear power plants (NPPs). In order to identify the influencing relationships and extent between TSA and PSFs, a model is needed to describe and correlate them. Firstly, based on TSA cognitive process, the main PSFs influencing the level of TSA are identified, including team knowledge and experience level, information display quality, attention and attitude, and team stress level. Then a conceptual model of TSA influencing factors is proposed to explore the path relationships and influencing mechanism between TSA and PSFs, and a structural equation model (SEM) that relates TSA to its PSFs is developed subsequently. Finally, by analyzing human factor events and small deviation reports, data from 178 samples were obtained and substituted into the structural equation model to analyze and identify the relationships between the PSFs. The results show that the preceding PSFs have significant effects on TSA. Based on path coefficients, positive effects were: team knowledge and experience level (0.504), information display quality (0.370), attention and attitude (0.249). Negative effect was: team stress level (-0.384). The results of this study can provide a theoretical basis for the prevention and control of TSA errors, and a qualitative analysis model for the quantitative evaluation of TSA reliability.